Structured reporting in the characterization of renal cysts by Contrast-Enhanced Ultrasound (CEUS) using the bosniak classification system: improvement of report quality and interdisciplinary communication - Schnitzer, Moritz Ludwig; Sabel, Laura; Schwarze, Vincent; Marschner, Constantin; Froelich, Matthias F.; Nuhn, Philipp; Falck, Yannick; Nuhn, Maria-Magdalena; Afat, Saif; Staehler, Michael; Rückel, Johannes; Clevert, Dirk-André; et al. (Diagnostics, 2021)
Background: This study aims to evaluate the potential benefits of structured reporting (SR) compared to conventional free-text reporting (FTR) in contrast-enhanced ultrasound (CEUS) of cystic renal lesions, based on the Bosniak classification. Methods: Fifty patients with cystic renal lesions who underwent CEUS were included in this single-center study. FTR created in clinical routine were compared to SR retrospectively generated by using a structured reporting template. Two experienced urologists evaluated the reports regarding integrity, effort for information extraction, linguistic quality, and overall quality. Results: The required information could easily be extracted by the reviewers in 100% of SR vs. 82% of FTR (p < 0.001). The reviewers trusted the information given by SR significantly more with a mean of 5.99 vs. 5.52 for FTR (p < 0.001). SR significantly improved the linguistic quality (6.0 for SR vs. 5.68 for FTR (p < 0.001)) and the overall report quality (5.98 for SR vs. 5.58 for FTR (p < 0.001)). Conclusions: SR significantly increases the quality of radiologic reports in CEUS examinations of cystic renal lesions compared to conventional FTR and represents a promising approach to facilitate interdisciplinary communication in the future.
Gesehen am 01.07.2021